Chinese dream in XXI century (Journal of Philosophy Culture and Political Science, 2019)
Today, we often hear the idea that the 21st century is the age of China, and humanity is beginning to get used to this information. The path of development of the People’s Republic of China, initiated by Mao Zedong, retaining the continuity of generations, continuing today Xi Jingping enters a special period. Headed by Xi Qinping, strengthening their place in the world arena, representatives of the «fifth generation» often talk about the «Great Chinese Dream». To implement this goal, concrete programs and plans have been adopted at the state level, and their phased implementation is expected. Moreover, a specific chronological framework for achieving the result has been approved. If by 2021, to the 100th anniversary of the Chinese Communist Party, it is planned to become a state with an average profit, then by the year 2049, to the 100th anniversary of the formation of the People’s Republic of China, it isplanned to become a global superpower and fully realize the Chinese dream. Of course, it is important for each nation to have their own dream and better that they will come true. But, how will the «Chinese dream» affect the world? Can the realization of the dream of one nation harm the wishes of another nation!?Key words: Chinese dream, People’s Republic of China, Xi Jinping, China’s foreign policy, Clash of civilizations.